2010
DOI: 10.2478/s11536-009-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anemia associated in-hospital mortality and morbidity in isolated coronary artery bypass graft surgery

Abstract: AbstractAnemia is an indisputable finding in patients scheduled for coronary artery bypass graft (CABG) that can occur any time preoperatively. In presence of severe coronary artery disease, anemia can dramatically affect surgical outcomes. Therefore, we conducted this study to determine the effect of low preoperative hemoglobin (Hgb) on postoperative outcome in patients who underwent coronary artery bypass graft (CABG). In all, 4432 patients who had undergone isolated CABG at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Characteristics of the included studies are summarized in Table . A total of 949 445 patients were included, and all 24 studies reported the primary outcome of 30‐day or in‐hospital mortality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies are summarized in Table . A total of 949 445 patients were included, and all 24 studies reported the primary outcome of 30‐day or in‐hospital mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, stroke and myocardial infarction were reported as an outcome only in studies of patients undergoing cardiac surgery ( Table ). A haemoglobin definition was used in 17 studies, a haematocrit definition in six studies, and both definitions were used in one study. Definitions of anaemia ranged from a haemoglobin concentration of 11 to 12 g/dl or a haematocrit of 30–39 per cent for female patients, and from 11 to 14 g/dl or 30–39 per cent respectively for male patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations